The Dundrum Toolkit. Dangerousness, Understanding, Recovery and Urgency Manual (The Dundrum Quartet). Four Structured Professional Judgement Instruments for Admission Triage, Urgency, Treatment Completion and Recovery Assessments - KENNEDY, HARRY; O'NEILL, CONOR (Trinity College Dublin, 2010)
The DUNDRUM QUARTET: This handbook describes a suite of four structured professional judgement instruments. These structured professional judgement instruments are intended to provide a validated and transparent means of making decisions about admission, transfer and discharge in forensic mental health / psychiatry services. The DUNDRUM-1 triage security items are designed for the assessment of need for therapeutic security based on patient characteristics. Patients can be rated according to their need for high, medium, low or no therapeutic security. The DUNDRUM-2 truage urgency items are intended to aid the prioritising of patients on a waiting list for admission to a therapeutically secure hospital. The DUNDRUM-3 programme completion items describe the extent to which patients in a forensic secure hospital have engaged successfully in treatments under five `pillars? of care or domains relevant to reducing and managing risk of harm. These five domains are physical health, mental health, drugs and alcohol problems, problem behaviours and family, social and occupational function. The DUNDRUM-4 recovery items are intended to provide a structured professional judgement instrument for assessing the extent to which a person is ready to move to a less secure placement, based on stability, insight, rapport and working alliance, leave and dynamic risk.
PUBLISHED
Dublin, Ireland
Keywords: violence risk assessment; forensic psychiatry